2017
DOI: 10.1111/apm.12785
|View full text |Cite
|
Sign up to set email alerts
|

Localization of surfactant protein‐D in the rheumatoid synovial membrane

Abstract: Surfactant protein-D (SP-D) is a collectin, which plays an important role in airway protection and inflammation. The molecule has both pro-and anti-inflammatory capacities depending on its molecular size. Its involvement in joint diseases is largely unknown and the aim of this investigation was to study SP-D occurrence and distribution in the synovial membrane of patients with long-standing rheumatoid arthritis (RA) and osteoarthritis (OA). Six RA patients and six OA patients, who underwent total hip arthropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Furthermore, its presence has been demonstrated in healthy lacrimal gland, conjunctiva, cornea, and nasolacrimal duct samples ( 6 ). Other studies have shown the presence of SP-D in synovial fluid derived from patients with rheumatoid arthritis ( 7 ).…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, its presence has been demonstrated in healthy lacrimal gland, conjunctiva, cornea, and nasolacrimal duct samples ( 6 ). Other studies have shown the presence of SP-D in synovial fluid derived from patients with rheumatoid arthritis ( 7 ).…”
Section: Introductionmentioning
confidence: 91%
“…SP-D is primarily synthesized and secreted into the airspace of the lungs by alveolar type II and Clara cells, with a key role in surfactant homeostasis by reducing surface tension ( 6 ). However, its extrapulmonary existence is well-established now, ranging from the mucosa of the gastrointestinal and reproductive tracts (including ovaries) and nasal cavity to the brain and in various exocrine ducts ( 8 , 9 ), conjunctiva, cornea, lacrimal gland, nasolacrimal ducts ( 8 ), and synovial fluid ( 10 ). Protective effects of SP-D against a range of pathogens ( 6 , 11 ) and allergens ( 12 16 ) are well-documented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…1 Decreased SP-D levels in early RA may correlate negatively to RA disease activity measures 41 42 and may modulate inflammation in RA. 43 Increased serum microfibrillar-associated protein 4 (MFAP4) seem to reflect disease-induced processes, due to low heritability and relatively limited basal variation. 44 MFAP4 is found with especially high expression in the heart, small intestine and the lungs.…”
Section: Potential Blood Biomarkers (Ie Other Index Tests)mentioning
confidence: 99%
“… 1 Decreased SP-D levels in early RA may correlate negatively to RA disease activity measures 41 42 and may modulate inflammation in RA. 43 …”
Section: Introductionmentioning
confidence: 99%